Advanced materials on sample preparation for safety analysis of aquatic products. Issue 6 (2nd November 2020) - Lai, Huasheng; Li, Gongke; Zhang, Zhuomin
Abstract: Safety analysis of aquatic products has been a challenge in recent years due to the serious matrix interference, complex characteristics, and ultra‐low content of analytes. Introducing advanced materials to sample preparation technique can greatly improve the extraction, enrichment, and separation for further qualification and quantification of target analytes by coupling with consequent analytical technologies. Based on this scope, this review is mainly introducing advanced materials on the sample preparation for safety analysis of aquatic products in the past decade. After introducing the importance of the corresponding advanced materials, advanced materials are used for the sample preparation and in the improvement of safety analysis result of aquatic products. Advanced materials for sample preparation of aquatic products were reviewed including carbon materials, metal organic frameworks, covalent organic frameworks, molecularly/ions imprinted polymers, etc. Then, applications of the advanced materials for the analysis of specific fishery analytes (antibiotics, anesthetic, preservatives, etc.) were briefly introduced. Conclusions and perspectives on advanced materials for sample preparation and safety analysis of aquatic products were also presented.